SIÇAN TİROİD BEZİNDE KADMİYUM HASARINA KARŞI C VİTAMİNİ, E VİTAMİNİ VE SELENYUMUN KOMBİNE KULLANIMININ ETKİLERİ - KARABULUT-BULAN, Ömür; KOYUTÜRK, Meral; BOLKENT, Şehnaz; YANARDAĞ, Refiye; TABAKOĞLU-OĞUZ, Ayşe (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Histopathological alterations to various organs of the different species in acute and chronic cadmium exposure have been studied by light and electron microscopy. Metallothionein is a protein inducible by heavy metal ions. The aim of this study was to determine the effects of vitamin C, vitamin E and selenium combination on the cadmium-induced morphological and immunohistochemical changes in the thyroid gland of adult male rats. Results.- In the group given cadmium, the degenerative changes were observed in the thyroid gland. In addition, an increase in the number of metallothionein positive cells was detected in this group. These immunoreactive cells were identified as mast cells. While these degenerative changes and metallothionein immunoreactive cells in the thyroid gland were decreased in the group given cadmium and antioxidants according to the experimental group. Conclusion.- These results suggest that metallothionein participate in accumulation of cadmium in rats, since thyroid gland containing a lot of metallothionein positive cells show a tendency to accumulate of cadmium. In addition, the combination of vitamin C, vitamin E and selenium shows a protective effect against cadmium induced oxidative injury of thyroid gland. Antioxidants also may participate to regulation of the metallothionein expression.